Characteristic of the Source Rock Of The Lahat and Talang Akar With Crude Oil In Sarolangun, Jambi sub-basin, Indonesia - Alfayed, Muhammad Rus Dody; Siregar, Yusmansyah; Ramadani, Dinda Novia; Syaifudin, M.; Setiawan, Jatmika (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
The research location is situated in Sarolangun, Jambi Province, within the Jambi Sub-Basin. Oil has been produced in the Jambi Sub-Basin study area from Paleogene-Neogene aged source rocks. However, the success ratio of oil discovery in the Jambi Sub-Basin remains at 51%. This study aims to determine the geochemical aspects in characterizing the source rocks and oil. The data used for analysis include total organic carbon, rock pyrolysis, vitrinite reflectance, and biomarkers.Geochemical characterization of the Lahat Formation source rock reveals a kerogen type II-III, generating oil and gas, while the Talang Akar Formation has a kerogen type II, producing oil, and the upper part of the Talang Akar Formation also has a kerogen type II, generating oil. The Lahat Formation biomarker consists of higher plants and algae in anoxic conditions, with high C29 sterane and early mature Tm/Ts ratio. The lower part of the Talang Akar Formation biomarker has lacustrine-marine algae organic material in anoxic conditions, with high C27 sterane and early mature Tm/Ts ratio. The upper part of the Talang Akar Formation biomarker has higher plant and marine algae organic material, with high oleanane and early mature Tm/Ts ratio. The produced oil has biomarker characteristics indicating deposition in anoxic conditions, with a mix of algae-higher plant organic material, and early mature Tm/Ts ratio. Based on these results, the oil is positively correlated with the Talang Akar Formation, indicating that the organic material originates from a marine or lacustrine depositional environment.